TINJAUAN PERENCANAAN GEOMETRIK JALAN STUDI KASUS PADA RUAS JALAN PROVINSI REMBIGA (BATAS KOTA)–PEMENANG - WIRA SAKTI KUSUMA; LALU HARDI WIJAYA; AMINULLAH AMINULLAH (LPPM PSDKU Kampus Mataram UNMAS Denpasar, 2022)
The purpose of this study Mevaluates geometric design on the road section of Rembiga Province (City Boundary)–Winner in accordance with the planning, mengevaluation of the magnitude of the alinyemen Horizontal on the road section of Rembiga Province (City Boundary)–Winner, determinethe length of the ideal transition ramp according to the Standard geometric design of intercity roads, this type of research using quantitative approach research is descriptive, data analysis using equations in accordance with the Geometric Planning Procedures of The Road 1997 (TPGJAK No.038/TBM/1997) The results of this study showed that, the fingers on the road of Rembiga Province (City Boundary)–The winner at each corner I 59618, turn II 58.545, turn III 54.833, turn IV 56.708, and bend V 57.325 smaller thanthe minimum radius(Rc) 60 m smaller than the radius allowed, Rembiga Province road section (City Boundary)–Winner after the calculation obtained the percentage of slope, which is 9,648 %, greater 3 % allowed, At turn I obtained the length of the arc circle Lc = 26 m, bend II Lc = 48 m. bend III = 22 m, bend IV = 92 m, and tikunga V = 34 m, then from the evaluation results carried out should be the length of the arc circumference Lc at turn I Lc = 26.167 m , bend II = 49,193 m, bend III = 24,073 m, bend IV = 97,340 m, and bend V = 35,587 m, this designates the rembiga province road (City Boundary)–The winner is quite dangerous because many geometric bends are not in accordance with the guidelines of Bina Marga.